Toxicity and biodistribution comparison of functionalized nanodiamonds, quantum dot nanocarbons and gold nanoparticles - Alexander, Elena; Leong, Kam W. (Frontiers in Nanotechnology, 2025)
IntroductionNanomaterials are extensively utilized in applications ranging from electronics to biomedical therapies; however, their widespread use has prompted concerns about potential toxicity in humans. Understanding the biodistribution and toxicity profiles of nanoparticles is crucial for their safe application.MethodsThis study assessed the dose-dependent toxicity and biodistribution of unconjugated nanodiamonds, nanobody-conjugated nanodiamonds, gold nanoparticles, and quantum dot nanocarbons in 22 female C57BL/6 mice. Nanoparticles were intravenously administered at concentrations of 5, 10, 20, and 40 mg/kg. Samples were collected at 2, 24, and 96 hours post-administration to evaluate tolerability, immune responses, and biodistribution patterns.ResultsUnconjugated nanodiamonds showed favorable tolerability, eliciting minimal inflammatory responses and significantly lower memory T cell activation compared to gold nanoparticles and quantum dot nanocarbons. Nanobody-conjugated nanodiamonds triggered moderate inflammation at 2 hours post-dosing. Specifically, CD69 expression in CD8+ T cells was highest in the gold nanoparticle group (mean: 0.40 ± 0.16) and lowest in the unconjugated nanodiamond group (mean: 0.12 ± 0.09). CD25 expression was most elevated in quantum dot nanocarbons (mean: 0.23 ± 0.04) and lowest in nanobody-conjugated nanodiamonds (mean: 0.09 ± 0.04). Total T cells were highest in the nanobody-conjugated group (mean: 49.10% ± 6.99) and lowest in the unconjugated nanodiamond group (mean: 40.70% ± 8.10). Nanodiamonds primarily accumulated in the heart, whereas gold nanoparticles localized mainly in the left lung, and quantum dot nanocarbons predominantly persisted in the kidney, liver, blood, and heart.DiscussionThese results indicate that nanodiamonds exhibit favorable tolerability and controlled immune responses compared to gold nanoparticles and quantum dot nanocarbons, highlighting their potential as safer nanomaterials for biomedical applications.